Pengaruh Kinerja Keuangan dan Struktur Modal terhadap Harga Saham : Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Safii, Mohamad; Wulandari, Provita; Surahman, Hendy; Zannah, Ainun (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
The share price is the selling price of a banking company placed by the capital market and is important for every bank because it reflects the value of the bank itself. This research aims to test and prove the influence of financial performance and capital structure on share prices (empirical study on banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period). The type of research used is a quantitative method. The type of data used is secondary data in the form of financial reports of banking companies listed on the Indonesia Stock Exchange for the 2018-2022 period. Samples were collected using the purposive sampling method. The number of companies used as research samples was 26 out of 47 banking companies with a research period of 5 years of observation, so that a total of 130 research samples were obtained. Data processing used the Eviews 10 Statistical Program. Furthermore, various tests were carried out including descriptive statistical tests, model tests, model selection, classical assumption testing and hypothesis testing, so that the research test results prove that financial performance and capital structure simultaneously influence the price of banking shares listed on the Indonesia Stock Exchange for the 2018-2022 period. Financial performance partially has a significant effect on share prices. Meanwhile, capital structure partially has no effect on banking share prices listed on the Indonesia Stock Exchange for the 2018-2022 period.